Relações entre a motivação para o trabalho voluntário e as práticas de cidadania: uma análise com conselheiros do orçamento democrático do estado da Paraíba - Leite, Stella Pereira (2023)
This dissertation aims to understand the relationship between motivation for volunteer work and citizenship practices, focusing on councilors who work in the Democratic Budget in the state of Paraíba. This work follows a model of structure in the format of articles, consisting of a set of four interdependent studies: Study I comprised a literature review investigating the main studies relating to citizenship and volunteering; Study II covers research into the motivation for volunteer work by councilors; Study III looked at the citizenship actions developed by councilors; and Study IV included an analysis of the relationships between motivation for volunteer work and citizenship practices. The method consisted of an integrative literature review in the Web of Science, SPELL and SciELO databases using Iramuteq for qualitative data analysis, followed by a quantitative approach to describe motivations for volunteering and citizenship practices. The research was carried out using a questionnaire, applying a scale based on the Structural Model of Motivation in Volunteer Work proposed by Cavalcante (2016) and another based on the Citizenship Practices Scale proposed by Caldas (2020). The findings are consistent with previous studies which indicate that voluntary action is positively related to the understanding and exercise of active citizenship. On the other hand, it identifies altruistic and affiliation motivations as the main explanatory forces for the citizen behavior of the volunteers surveyed, and selfish motivations as absent in the conduct of citizen behavior, in the civil, political and social dimensions.